A‐Fibers Mediate Cold Hyperalgesia in Patients with Oxaliplatin‐Induced Neuropathy. Issue 6 (2nd February 2018) - Forstenpointner, Julia; Oberlojer, Violetta C.; Naleschinski, Dennis; Höper, Johanna; Helfert, Stephanie M.; Binder, Andreas; Gierthmühlen, Janne; Baron, Ralf
Abstract: Cold hyperalgesia is a common side effect of oxaliplatin treatment; still, the pathophysiological and molecular mechanisms as well as the contribution of different primary afferent fiber systems are unclear. Therefore, patients with oxaliplatin‐induced acute neuropathy with ( n = 6) and without ( n = 7) cold hyperalgesia were tested by applying a preferential blockade of peripheral myelinated A‐fiber afferents in combination with quantitative sensory testing. Additionally, an interview‐based questionnaire assessed the severity of symptoms and the impact on daily activities. Results indicate a deficit of cold perception in patients without cold hyperalgesia compared to patients with cold hyperalgesia prior to A‐fiber blockade. In patients with cold hyperalgesia, a preferential blockade of A‐fibers abolished cold hyperalgesia. This suggests that oxaliplatin‐induced cold hyperalgesia is mediated by A‐fibers and that a deficit in A‐fiber function might prevent the development of cold hyperalgesia. The work supports findings in rodents and in human sural nerve biopsies indicating that oxaliplatin interferes with axonal ion conductance in intact A‐fibers by sensitizing potassium and/or sodium channels. Drugs that act on these molecular targets might be of potential value to treat oxaliplatin‐induced cold hyperalgesia.